2013
DOI: 10.1177/1049731512466312
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Differential Response

Abstract: Differential response (DR), also referred to as alternative response (AR), family assessment response (FAR), or multiple track response, was developed to incorporate family-centered, strengths-based practices into child protective services (CPS), primarily by diverting lower risk families into an assessment track rather than requiring the traditional CPS investigation. Since the program's inception, researchers have conducted several large evaluation studies of DR programs, and a large body of research and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…particularly related to children's safety'' (Hughes, Rycus, Saunders-Adams, Hughes, & Hughes, 2013, p. 495). Hughes et al (2013) highlight a number of trends and issues denoted by other authors (Child Welfare Information Gateway, 2008;Connolly, 2005;Lohrbach, 2011; National Quality Improvement Center on Differential Response in Child Protective Services, [NQIC-DR] 2011;Schene, 2005;Waldfogel, 2009;Yuan, 2005) . Within their review, the authors have identified one of the prevailing contradictions and conflicts constraining any child welfare system: ''The confluence in both law and policy of these compelling practice principles reflected one of the most prevalent and difficult inherent tensions in CPS practice: that is, how to promote engagement, empowerment, and support of families without compromising the essential need and capacity to use more authoritative interventions to protect children at high risk of serious harm when less authoritative methods could not'' (Hughes et al, 2013, p. 494).…”
Section: Value Utility and Support For Drmentioning
confidence: 97%
“…particularly related to children's safety'' (Hughes, Rycus, Saunders-Adams, Hughes, & Hughes, 2013, p. 495). Hughes et al (2013) highlight a number of trends and issues denoted by other authors (Child Welfare Information Gateway, 2008;Connolly, 2005;Lohrbach, 2011; National Quality Improvement Center on Differential Response in Child Protective Services, [NQIC-DR] 2011;Schene, 2005;Waldfogel, 2009;Yuan, 2005) . Within their review, the authors have identified one of the prevailing contradictions and conflicts constraining any child welfare system: ''The confluence in both law and policy of these compelling practice principles reflected one of the most prevalent and difficult inherent tensions in CPS practice: that is, how to promote engagement, empowerment, and support of families without compromising the essential need and capacity to use more authoritative interventions to protect children at high risk of serious harm when less authoritative methods could not'' (Hughes et al, 2013, p. 494).…”
Section: Value Utility and Support For Drmentioning
confidence: 97%
“…Yet, in any scenarios under a traditional framework, service provision is not part of the role of social services, though service recommendations may accompany investigations and escalation of intervention may occur if voluntary compliance does not occur. Differential response systems were developed to incorporate family centered practices into child protective services (Hughes, Rycus, Saunders-Adams, Hughes, & Hughes, 2013). Lower risk families are diverted into an assessment track in an attempt to enhance a parent's ability to safely care for their children (Hughes et al, 2013).…”
Section: Alternative Responsementioning
confidence: 99%
“…Differential response systems were developed to incorporate family centered practices into child protective services (Hughes, Rycus, Saunders-Adams, Hughes, & Hughes, 2013). Lower risk families are diverted into an assessment track in an attempt to enhance a parent's ability to safely care for their children (Hughes et al, 2013). Alternative response systems-also known as differential response, dual track, multiple track, or family assessment-allow state child protective services to provide different responses to reports of child maltreatment (Merkel-Holguin, 2005).…”
Section: Alternative Responsementioning
confidence: 99%
See 2 more Smart Citations